(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Sleep is a basic human need, important for good health & therefore considered as one of the Trividh upastambhas. Sleep is a natural phenomenon of giving adequate rest to the body and mind. Sleep disturbances increase with aging and it is estimated that nearly 67% of the elderly people have at least one sleep-related complaint. Various sleep disorders identified in elderly people include long time to fall asleep, disturbed sleep at night (Khandit nidra) and insomnia (Anidra). An improper diet and lifestyle causes aggravation of Vata that travels through the channels of the head causing sleeplessness. Suppressed emotions, disturbed sleeping patterns, worries, anger, overexcitement and ill health may be other responsible factors for sleep disorders. Abhyanga & Sanvahan (massage), Udsadan, Udvartan (Rubbing medicated paste & powder), Snana (bath), Karnapuran & Akshitarpan, Shirobhyanga & Padabhyanga, Shirodhara, Takra dhara etc are desirable for best results in management of sleep disorders. Yoga with a combination of Asanas specifically Shavasana, Pranayam, and meditation (Dhyan) along with proper, balanced diet & lifestyle giving due respect to the biological clock proves beneficial. Yoga is considered to be a means for physical, mental and spiritual growth of an entity. So, it is found that the complete package of palliative, Panchakarma treatment, Yoga-pranayama provides good results in elderly sleep disorders.